Optical Read-out of Neural Activity in Mammalian Peripheral Axons: Calcium Signaling at Nodes of Ranvier - Arjun K. Fontaine (Nature Portfolio, 2017)
Abstract Current neural interface technologies have serious limitations for advanced prosthetic and therapeutic applications due primarily to their lack of specificity in neural communication. An optogenetic approach has the potential to provide single cell/axon resolution in a minimally invasive manner by optical interrogation of light-sensitive reporters and actuators. Given the aim of reading neural activity in the peripheral nervous system, this work has investigated an activity-dependent signaling mechanism in the peripheral nerve. We demonstrate action potential evoked calcium signals in mammalian tibial nerve axons using an in vitro mouse model with a dextran-conjugated fluorescent calcium indicator. Spatial and temporal dynamics of the signal are presented, including characterization of frequency-modulated amplitude. Pharmacological experiments implicate T-type CaV channels and sodium-calcium exchanger (NCX) as predominant mechanisms of calcium influx. This work shows the potential of using calcium-associated optical signals for neural activity read-out in peripheral nerve axons.